Ammonia Volatilization and Marandu Grass Production in Response to Enhanced-Efficiency Nitrogen Fertilizers - Cassimiro, Juliana Bonfim [UNESP]; de Oliveira, Clayton Luís Baravelli; Boni, Ariele da Silva [UNESP]; Donato, Natália de Lima [UNESP]; Meirelles, Guilherme Constantino [UNESP]; da Silva, Juliana Françoso [UNESP]; Ribeiro, Igor Virgilio [UNESP]; Heinrichs, Reges [UNESP] (MDPI, 2023)
The objective of this study was to evaluate dry matter (DM) production of Urochloa brizantha cv. Marandu and ammonia volatilization in response to rates and sources of enhanced-efficiency N fertilizers. The experiment was took place in a pasture area, two growing seasons. A randomized block design with four replications was used, in a 4 × 2 + 1 factorial arrangement, consisting of four N sources (Urea—UrConv; Ammonium nitrate—AN; Urea + NBPT—UrNBPT; Urea + Duromide—UrDuromide) and two nitrogen rates (100 and 200 kg ha−1 year), plus a treatment without nitrogen fertilization (control). At both N rates, ammonia volatilization from UrConv100/200 was greatest. Ammonia volatilization was less after UrNBPT and UrDuromide application, with values similar to AN. Ammonia losses from UrDuromide tend to be lower than from UrNBPT. The N use efficiency in dry matter production of Marandu was influenced by the N sources and rates. At both N rates, the efficiency of UrDuromide and UrNBPT was greater than that of UrConv. With regard to total DM and leaf percentage in response to N rates, DM production increased after 200 kg N ha−1 rates in response to all sources, in both years. The UrDuromide reduce N losses by volatilization compared to UrNBPT and Urconv, and resulted in greater total DM production and relative leaf production of Marandu, in comparison to UrNBPT, AN and Urconv.
Keywords: dry matter production; Duromide; pasture; urease inhibitor; Urochloa brizantha